Impact of coexistent adenomyosis on outcomes of patients with endometrioid endometrial cancer: a propensity score-matched analysis. Issue 1 (January 2018) - Aydin, Hulya Ayik; Toptas, Tayfun; Bozkurt, Selen; Pestereli, Elif; Simsek, Tayup
Purpose: Despite the common occurrence of adenomyosis in endometrial cancer (EC), there is a paucity and conflict in the literature regarding its impact on outcomes of patients. We sought to compare outcomes of patients with endometrioid type EC with or without adenomyosis. Methods: A total of 314 patients were included in the analysis. Patients were divided into 2 groups according to the presence or absence of adenomyosis. Adenomyosis was identified in 79 patients (25.1%). A propensity score-matched comparison (1:1) was carried out to minimize selection biases. The propensity score was developed through multivariable logistic regression model including age, stage, and tumor grade as covariates. After performing propensity score matching, 70 patients from each group were successfully matched. Primary outcome of the study was disease-free survival (DFS), and the secondary outcomes were overall survival (OS) and disease-specific survival (DSS). Results: Median follow-up time was 61 months for the adenomyosis positive group and 76 months for the adenomyosis negative group. There were no statistically significant differences in 3- and 5-year DFS, OS, and DSS rates between the 2 groups. Five-year DFS was 92% vs 88% (hazard ratio [HR] 1.54 [0.56-4.27]; p = 0.404), 5-year OS was 94% vs 92% (HR 1.60 [0.49-5.26]; p = 0.441), and 5-year DSS was 94% vs 96% (HR 2.51 [0.46-13.71]; p = 0.290) for patients with and without adenomyosis, respectively. Conclusions: Coexistent adenomyosis in EC is not a prognostic factor and does not impact survival outcomes.